Analysis of Musculoskeletal Complaints and Work Fatigue in Dental Assistants - Negara, Ni Luh Gede Aris Maytadewi; Suarjana, I Wayan Gede; Prihastini, Komang Angga; Listiantari, Dwiastutik (Indonesian Journal of Global Health Research, 2024)
Dental assistants are one of the health workers who have the potential to experience musculoskeletal complaints and work fatigue due to repetitive and monotonous work in a sitting position. This study aims to determine musculoskeletal complaints and work fatigue experienced by dental assistants. This research is descriptive qualitative research, in which musculoskeletal complaints were evaluated from the results of the Nordic Body Map (NBM) questionnaire while work fatigue was evaluated from the results of the 30 item of rating scale questionnaire. This research was conducted at dental hospital XX, Denpasar, the number of respondents in this study were 20 dental assistant who were administratively recorded as serving at dental hospital XX, Denpasar. The research was conducted in April 2022. Respondents were asked to provide an assessment of the part of their body that felt sick during work activities. Based on the results of descriptive analysis showed that out of 20 respondents, 13 people (65%) had moderate musculoskeletal complaints, 5 people (25%) had high musculoskeletal complaints and 2 people (10%) had very high musculoskeletal complaints. The results of the study on the fatigue aspect showed that 16 people (80%) experienced moderate fatigue, 3 people (15%) experienced high fatigue and 1 person (5%) experienced very high fatigue. The conclusion in this study showed that musculoskeletal complaints and work fatigue due to repetitive and monotonous work in a sitting position to increase work stress factors.